2020
DOI: 10.1161/jaha.119.015799
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Serum Bilirubin and Risk of First Stroke in Hypertensive Patients

Abstract: Background Data on the association between serum bilirubin and the risk of stroke are limited and inconclusive. We aimed to evaluate the association between serum bilirubin and the risk of first stroke and to examine any possible effect modifiers in hypertensive patients. Methods and Results Our study was a post hoc analysis of the CSPPT (China Stroke Primary Prevention Trial). A total of 19 906 hypertensive patients were included in the final analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Finally, a total of 11 independent cohort studies (published in nine articles) were included in the meta-analysis (figure 1). 10–12 14 18–20 34 35…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a total of 11 independent cohort studies (published in nine articles) were included in the meta-analysis (figure 1). 10–12 14 18–20 34 35…”
Section: Resultsmentioning
confidence: 99%
“…Eleven independent cohort studies examining the relationship between bilirubin levels and stroke risk (7835 cases among 263 596 individuals) were published between 2009 and 2020 (online supplemental table 2). Among these, two studies were primarily conducted in the USA,11 14 four in Asian countries (China and Korea) 10 18–20 and three in European countries 12 34 35. The size of individuals ranged from 316 (in the study conducted by Liu et al 19) to 96 381 (in the study conducted by Marconi et al 14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that decreased bilirubin levels are associated with asymptomatic intracranial atherosclerosis 32 and cerebral infarction. 58 Exploring the relationship between bilirubin and CAS can inspire clinicians on cerebral infarction prevention and treatment. The levels of TBIL and UCB were negatively correlated with the CAS process, and the association of UCB was stronger, whereas the level of CB was positively correlated with CAS.…”
Section: Discussionmentioning
confidence: 99%